Mentoring Principles, Processes, and Strategies for Facilitating Mentoring Relationships at a Distance - Kalyani Premkumar; Angie Wong (Association of American Medical Colleges, 2010)
Abstract This web-based learning platform was developed for use by faculty and students who wish to learn about and engage in mentor/mentee relationships. Mentoring is a learning process where helpful, personal, and reciprocal relationships are built while focusing on achievement, and providing emotional support. Within mentoring relationships, mentees develop and learn through conversations with more experienced mentors who share knowledge and skills that can be incorporated into their thinking and practice. This platform has been evaluated by four representatives from the target audience, and all agreed or strongly agreed that it was very useful, specifically in their practice. The content of this platform is not only applicable to medical and dental educators, but for anyone wanting to learn about mentoring or start a program in mentoring. Future plans include making the platform more interactive by introducing a Wiki-style interface, so that the target audience can share their experiences and add to the resource.